2021
DOI: 10.1038/s41386-021-01168-2
|View full text |Cite
|
Sign up to set email alerts
|

Release of endogenous dynorphin opioids in the prefrontal cortex disrupts cognition

Abstract: Following repeated opioid use, some dependent individuals experience persistent cognitive deficits that contribute to relapse of drug-taking behaviors, and one component of this response may be mediated by the endogenous dynorphin/kappa opioid system in neocortex. In C57BL/6 male mice, we find that acute morphine withdrawal evokes dynorphin release in the medial prefrontal cortex (PFC) and disrupts cognitive function by activation of local kappa opioid receptors (KORs). Immunohistochemical analyses using a pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 61 publications
2
40
0
Order By: Relevance
“…Based on the data mentioned above, the present results may demonstrate that the frequent injection of morphine and the subsequent overflow of dopamine in the target areas may gradually increase Pdyn expression, which, in turn, increases Penk expression via dopamine release re-duction and D2 dopamine receptor mechanism. The release of endogenous dynorphins in the prefrontal cortex disrupts cognition (55). Therefore, the increased expression of Pdyn in the PFC may be a possible explanation for cognitive impairments in morphine-dependent animals reported elsewhere (18,56).…”
Section: Discussionmentioning
confidence: 98%
“…Based on the data mentioned above, the present results may demonstrate that the frequent injection of morphine and the subsequent overflow of dopamine in the target areas may gradually increase Pdyn expression, which, in turn, increases Penk expression via dopamine release re-duction and D2 dopamine receptor mechanism. The release of endogenous dynorphins in the prefrontal cortex disrupts cognition (55). Therefore, the increased expression of Pdyn in the PFC may be a possible explanation for cognitive impairments in morphine-dependent animals reported elsewhere (18,56).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, other studies have shown that KOR agonists disrupt cognition. Abraham et al (2021) found that dynorphin-induced KOR activation in the medial prefrontal cortex disrupted cognition in mice undergoing acute morphine withdrawal. Furthermore, U50,488 has been shown to inhibit novel object recognition in mice ( Paris et al, 2011 ), and SalA reduced motivation and increased processing deficits in rats that were made to complete a multi-choice serial reaction time task ( Nemeth et al, 2010 ).…”
Section: Diseases For Which the Kappa-opioid Receptors Has Therapeuti...mentioning
confidence: 99%
“…Along with other sensors of opioid signaling 11,27 , this study establishes the first genetically encoded fluorescent protein biosensor for an opioid drug, enabling real-time quantification. Furthermore, the enantioselectivity encourages biosensor development to investigate "chiral switching" of other drugs where a single enantiomer substitutes a clinically used racemate 28 .…”
Section: Below))mentioning
confidence: 99%